RF engineering for wireless networks : hardware, antennas, and propagation - Dobkin, Daniel Mark (Communications engineering series., 2005)
Finally, here is a single volume containing all of the engineering information needed to successfully design and implement any type of wireless network! Author Dan Dobkin covers every aspect of RF engineering necessary for wireless networks. He begins with a review of essential math and electromagnetic theory followed by thorough discussions of multiplexing, modulation types, bandwidth, link budgets, network concepts, radio system architectures, RF amplifiers, mixers and frequency conversion, filters, single-chip radio systems, antenna theory and designs, signal propagation, as well as planning and implementing wireless networks for both indoor and outdoor environments. The appendices contain such vital data as U.S., European, and Japanese technical and regulatory standards for wireless networks, measurements in wireless networks, reflection and matching of transmission lines, determining power density, and much more. The accompanying CD includes useful software tools such as a link budget calculator, a Smith Chart calculator and plotter, and radio chain analysis utilities. No matter what type of wireless network you designBluetooth, UWB, or even metropolitan area network (MAN)this book is the one reference you cant do without! The A-to-Z guide to wireless network engineeringcovers everything from basic electromagnetic theory to modulation techniques to network planning and implementation! Engineering and design principles covered are applicable to any type of wireless network, including 802.11, 802.16, 802.20, and Bluetooth. Discusses state-of-the-art modulation techniques such as ultra wideband (UWB) and orthogonal frequency-division multiplexing (OFDM).